Impact of parotid gland dose and patient-related factors on radiation damage to dental hard tissues - Ramona Schweyen; Jeremias Hey; Johannes Seidel; Andreas Wienke; Yvonne Paelecke-Habermann; Dirk Vordermark; Thomas Kuhnt (Elsevier, 2015)
Background/purpose: To evaluate whether radiation damage to dental hard tissues depends on patient-related factors in addition to irradiation dose on the spared parotid gland. Materials and methods: Seventy curatively irradiated patients with head and neck cancer underwent dental treatment prior to, during, and after radiotherapy. During a follow-up period of 24 months, damages to dental hard tissues were classified. Mean doses (Dmean) during spared parotid gland radiotherapy, patients' oral hygiene practice, and socioeconomic status were determined. Results: No carious lesions were observed in 30 patients (Group A), while sporadic and general carious lesions were noticed in 18 patients (Group B) and 22 patients (Group C), respectively. The Dmean of Group A (21.2 ± 11.00 Gy) was significantly lower than that of Group C (33.9 ± 9.9 Gy; P < 0.001). Patients with an intermediate level of schooling qualification showed a higher risk for radiation caries than patients with higher education entrance qualification (P = 0.018). Conclusion: Radiation damage to dental hard tissues correlates with increased mean irradiation doses and a lower educational level.